Safety and efficacy of laparoscopic wedge gastrectomy for large gastrointestinal stromal tumors. Issue 4 (April 2017) - Milone, M.; Elmore, U.; Musella, M.; Parise, P.; Zotti, M.C.; Bracale, U.; Di Lauro, K.; Manigrasso, M.; Milone, F.; Rosati, R.
Abstract: Background: Although the feasibility of minimally invasive resection of small gastric GISTs is well established, less is known about safety and efficacy of laparoscopic surgery for large tumors. Methods: A retrospective analysis was performed, using a prospectively maintained comprehensive database. Patients were divided into two groups according to tumor size: Case group with tumors > 5 cm and control group with tumors <5 cm. Hospital charts were reviewed, and various outcome measures recorded, including operative time, estimated operative blood loss, post-operative leak, stasis, infection and recurrence. Results: No tumors were ruptured during surgical manipulation and no major morbidity or mortality occurred in either group. Operative time (75, 8 ± 33, 1 min in large cases vs 75, 8 ± 33, 1 min in small cases) was similar in both groups (p = 0, 61). The incidence of post-operative complications did not differ between the two groups. In details there were 21 out of 25 (84%) uncomplicated cases among small GISTs versus 17 out of 24 (70, 8%) uncomplicated cases among large GISTs (p = 0, 32). Conclusion: This matched-pair case control study demonstrates that laparoscopic wedge resection for large gastric GISTs is safe and effective, as demonstrated for small tumors.